A High-Quality Reference Genome Sequence and Genetic Transformation System of Aralia elata - Liu, Wenxuan; Guo, Wenhua; Chen, Song; Xu, Honghao; Zhao, Yue; Chen, Su; You, Xiangling (Frontiers in Plant Science, 2022)
Aralia elata is a perennial woody plant of the genus Aralia in the family Araliaceae. It is rich in saponins and therefore has a wide range of pharmacological effects. Here, we report a high-quality reference genome of A. elata, with a genome size of 1.21 Gb and a contig N50 of 51.34 Mb, produced by PacBio HiFi sequencing technology. This is the first genome assembly for the genus Aralia. Through genome evolutionary analysis, we explored the phylogeny and whole genome duplication (WGD) events in the A. elata genome. The results indicated that a recent WGD event occurred in the A. elata genome. Estimation of the divergence times indicated that the WGD may be shared by Araliaceae. By analyzing the genome sequence of A. elata and combining the transcriptome data from three tissues, we discovered important genes related to triterpene saponins biosynthesis. Furthermore, based on the embryonic callus induction system of A. elata established in our laboratory, we set up the genetic transformation system of this plant. The genomic resources and genetic transformation system obtained in this study provide insights into A. elata and lays the foundation for further exploration of the A. elata regulatory mechanism.